Subjective and objective survey of office lighting: effects on alertness, comfort, satisfaction, and safety - Rasouli Kahaki, Zeinab; Jahangiri, Hamid; Smith, Andrew P; Kazemi, Reza (La Medicina del Lavoro, 2022)
Background: Lighting is one of the workplace factors that can relevantly impact workers’ health, performance, safety, and job satisfaction. Brightness, natural light and color temperature are the factors that affect the quality of lighting. This study involved subjective and objective evaluation of office lighting and its effects on workers’ alertness, comfort, satisfaction, safety, and performance in a prominent government office. Methods: Visual comfort, alertness, performance, safety and satisfaction were assessed subjectively using the questionnaires and rating scales. Moreover, illuminance, color temperature of light sources, and natural light availability were evaluated objectively. Results: The findings of this study indicated that the use of natural light in the workplace could increase the illuminance and color temperature of light in the workplace and improve alertness, visual comfort, satisfaction and worker’s preference. Conclusions: To improve the quality of lighting in the workplace, factors affecting it, such as the color temperature and the availability of natural light, should be considered.